Yeh aur woh - Ghazala, Nomani; Shamsha, Hasan (Ferozsons Karachi, 1997)
"Yeh aur Woh" is a captivating exploration of contrasts and similarities. Through vivid storytelling and insightful analysis, this book delves into the complexities of human nature and societal dynamics. By examining diverse perspectives and experiences, it invites readers to challenge their own assumptions and embrace the beauty of difference.